Clinical outcomes and molecular typing of heterogenous vancomycin-intermediate Staphylococcus aureus bacteremia in patients in intensive care units. Issue 1 (December 2015) - Hu, Han-Chung; Kao, Kuo-Chin; Chiu, Li-Chung; Chang, Chih-Hao; Hung, Chen-Yiu; Li, Li-Fu; Liu, Tsui-Ping; Lin, Lee-Chung; Chen, Ning-Hung; Huang, Chung-Chi; Yang, Cheng-Ta; Lu, Jang-Jih
Abstract Background Staphylococcus aureus is one of most common pathogens in humans. Methicillin-resistantS. aureus (MRSA) accounts for 64 % ofS. aureus bacteremia isolated in intensive care units (ICUs), and heteroresistant vancomycin-intermediatesS. aureus (hVISA) is a phenotype of MRSA. However, studies focusing on the hVISA impact on critically ill patients are scarce. Methods This was a retrospective study conducted in a tertiary medical center from January 2009 to December 2010. All adult patients in ICUs with MRSA bloodstream infection were eligible. A modified population analysis profile and area under the curve method was applied to all isolates to confirm hVISA phenotype. Multilocus sequence typing (MLST), staphylococcal cassette chromosomemec (SCCmec ) and the accessory gene regulator (agr ) typing were performed individually. Clinical outcomes including in-hospital mortality, length of stay in intensive care unit and hospital after MRSA bacteremia of the patients were also analyzed. Results A total of 48 patients were enrolled and 14 patients were confirmed to have the hVISA phenotype. The prevalence of hVISA was 29.2 %. There was no difference in the age, sex, comorbidity, Charlson's comorbidity score and previous vancomycin therapy between the hVISA and VSSA groups. The hVISA group had a significantly higher in-hospital mortality than the VSSA group (13/14 versus 22/34;p = 0.046). All of the 14 hVISA patients had an MIC = 2 mg/L by E-test and this represented a significant association between high MIC and the development of hVISA (p < 0.001). MLST analysis showed all the isolates in the hVISA group were ST239, while ST239 (14/34; 41.2 %) and ST5 (12/34; 35.3 %) were predominant in the VSSA group (p = 0.007). A comparison of the survivor and non-survivor group showed that the hVISA phenotype (OR 11.8; 95 % CI 1.1–126.99;p = 0.042) and sequential organ failure assessment (SOFA) score (OR 1.39; 95 % CI 1.07–1.81;p = 0.014) were independent factors significantly associated with in-hospital mortality. Conclusions Patients in ICUs with MRSA bacteremia may have a higher in-hospital mortality if they have the hVISA phenotype. SOFA score is also predictor of mortality.